The role of relational marketing on the consumer buying decision of travel agencies - Silva, Vítor (2019)
Through the characterization of relational marketing, this study intends to understand how it can be influential in the purchase decision of the consumer in the context of travel agencies. The study analyzes how relational interaction occurs between clients and companies in the industry, perceiving how companies use relational marketing as a market strategy, and whether this is an influencing factor in consumer decision making. Exploratory interviews with directors of travel and tourism agencies were carried, with the objective of understanding the relevance of using relational marketing in the creation and maintenance of the clients of the companies they manage. The results point out that the use of relations as a source of value in the business of travel agencies is common and is seen by companies as a way to fight the increasing virtual competition in the market, being the relationship with the client seen as a differentiating and a positive influencing factor. From the point of view of the consumer, the relationship with the travel agent is seen as an element that increases confidence in the product acquired, being considered also by the consumers as a positive influencing factor. This research focused on the analysis of a very modern and pertinent problem, namely the threat of the new business model of the tour operators with their increasing investment in direct sales to the consumer. It was very interesting to observe the way that the market of the travel agencies survives and how it wages on relationships with customers, becoming more competitive and consequently creating superior value for the customer. This study intended to be a contribution to the marketing of travel agencies, encouraging the debate about relational marketing and its importance in increasing the competitiveness of the sector. The aim of the study was to analyze the points of view of consumers and companies in order to foster this debate and to understand the points of convergence between the two parts.